Wear Analysis on Silicon Carbide Coated HSS Pin on SS Disc Substrate. (2015) - Venkatesh, R.; Rao, Vaddi seahagiri; Arunkumar, N.; Biswas, Sunil; kumar, R. Shoban
Abstract: Wear takes predominant role in reducing the cutting life time of tool materials. This investigation focuses on the influence of Silicon Carbide nanocoating on the HSS tool material. Silicon carbide powder was coated on the high speed steel pin by using physical vapour deposition (PVD) technique. The stainless steel was selected as a work piece material. The performance parameters like volume loss, wear rate, stresses developed and temperature rise were compared between coated high speed steel pin and uncoated high speed steel pin upon machining the stainless steel disc. The performance parameters were calculated by using coefficient of friction values which were obtained from the pin on disc test. Substantial resistance to wear has been achieved by the coating. Scanning electron microscope (SEM) Analysis and Energy dispersive analysis by X-ray (EDAX) were used as characterization techniques.